Pengaruh Alkalisasi terhadap Sifat Mekanis Komposit Polypropylene Daur Ulang / Serat Biduri - Herlin Arina; Devin Priyan Mardiansyah; Untung Prayudie (G-Tech: Jurnal Teknologi Terapan, 2025)
The expansion of the automotive sector has heightened the demand for polypropylene (PP), resulting in an increase in PP waste. Nonetheless, recycling frequently undermines the mechanical and physical qualities of polypropylene (PP). This problem can be resolved by augmenting recycled polypropylene (rPP) with natural fibers, such as biduri fiber (Calotropis gigantea), recognized for its low density, high tensile strength, and hydrophobic-oleophilic characteristics. A potassium hydroxide (KOH) alkali treatment enhances fiber wettability and polymer adhesion by eliminating non-cellulosic constituents, hence strengthening the link between biduri fiber and the rPP matrix. This study examines the mechanical properties of rPP composites reinforced with 2% w/w biduri fiber and different KOH concentrations (0%, 2.5%, and 5% w/w). The composites were constructed into a three-layer configuration with thicknesses of 1 mm and 2 mm. Recycled polypropylene sheets were fabricated by heating rPP granules to 190°C for five minutes, subsequently compressing at 300 kg/cm², and cooling to 100°C. The composite was created by interposing nonwoven biduri fiber sheets between two rPP sheets and subjecting the assembly to heating at 210°C under a pressure of 300 kg/cm² for 10 minutes. The mechanical properties were evaluated using dog-bone-shaped specimens for tensile and impact testing. The findings indicated substantial enhancements in impact strength (up to 54,95%) and tensile strength (up to 3,6%) with elevated KOH content; however, the melt flow rate diminished, signifying a compromise between enhanced strength and processability. These results endorse the utilization of rPP-biduri fiber composites as sustainable, mechanically superior materials.